Floor Failure Evolution Mechanism for a Fully Mechanized Longwall Mining Face above a Confined Aquifer. (13th January 2019) - Zhai, Jinghui; Liu, Danlong; Li, Gang; Wang, Fangtian
Abstract : In longwall mining, the risk of water inrushes from the floors of deeply buried coal seams is closely related to the degree and depth of the destruction for the mining floor. To analyze the main factors affecting floor failure and the evolution of such failures, this study considered the LW2703 working face of the Chengjiao Coal Mine in China, which is characterized by a large buried depth, complex fault structure, and high pressure from a confined aquifer. The characteristics affecting floor crack development depth were analyzed by considering friction angle, cohesion force, floor pressure, stress increase coefficient, and peak position. A FLAC3D simulation was performed to compare the degrees of floor damage that occurred for caving and backfilling methods during the mining process. High-density electrical detection was performed on-site and used to (1) determine the maximum depth range of the floor damage, (2) reveal the laws governing the evolution of damage in a mining floor, and (3) provide a reasonable basis for evaluating and preventing floor water inrush accidents.